2016
DOI: 10.1017/pab.2015.53
|View full text |Cite
|
Sign up to set email alerts
|

Compositional turnover and ecological changes related to the waxing and waning of glaciers during the late Paleozoic ice age in ice-proximal regions (Pennsylvanian, western Argentina)

Abstract: The late Paleozoic ice age (LPIA) had a profound effect on the biota. Despite much research having been focused on paleotropical regions or global-scale analyses, regional ecological changes have seldom been studied in ice-proximal basins. Here, I study the compositional turnover and diversity structure across the main Carboniferous glacial event recorded in western Argentina and the subsequent nonglacial interval. Brachiopod and bivalve data from western Argentina suggest that the transition from glacial to n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
43
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(46 citation statements)
references
References 101 publications
(189 reference statements)
1
43
1
1
Order By: Relevance
“…Further analyses on potential selectivity showed that turnover was not taxonomic nor environmentally homogeneous, being harsher in brachiopods and in offshore settings (Balseiro, 2016a). Moreover, while a severe taxonomic turnover, detected in brachiopods, was caused by higher extirpation (Balseiro, 2016a), a stronger turnover in the offshore was a result of higher immigration into that environment (Balseiro and Halpern, 2016), indicating that turnover in both cases was driven by contrasting dynamics.…”
Section: Accepted Manuscriptmentioning
confidence: 92%
See 4 more Smart Citations
“…Further analyses on potential selectivity showed that turnover was not taxonomic nor environmentally homogeneous, being harsher in brachiopods and in offshore settings (Balseiro, 2016a). Moreover, while a severe taxonomic turnover, detected in brachiopods, was caused by higher extirpation (Balseiro, 2016a), a stronger turnover in the offshore was a result of higher immigration into that environment (Balseiro and Halpern, 2016), indicating that turnover in both cases was driven by contrasting dynamics.…”
Section: Accepted Manuscriptmentioning
confidence: 92%
“…glacial centers James, 2008, 2012;Sterren and Cisterna, 2010;Balseiro, 2016a;Balseiro and Halpern, 2016).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations